Experimental study on flow and heat transfer characteristics of shark skin inspired heat exchange tubes and analysis of exergy and entransy properties - Jichen Sun; Hongguang Xiao; Xinwen Zhao; Wenzhen Chen; Kainan Jiang; Nan Zhang; Muzhen Li (Annals of Nuclear Energy, 2026)

Deciphering the mechanisms of polystyrene microplastic-induced toxicity in Litopenaeus vannamei: An integrated transcriptomic and microbiomic investigation - Miao Zhu; Xuejie Wang; Danqing Hou; Shan Gao; Jianbo Yu; Jichen Zhao; Chengbo Sun (Regional Studies in Marine Science, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Microbiomics and metabolomics analysis reveals the unsynchronized growth mechanism in kuruma shrimp (Marsupenaeus japonicus) - Jichen Zhao; Minze Liao; Miao Zhu; Bo Wang; Haipeng Qin; Chengbo Sun (Aquaculture, 2026)

Contrasting size responses of loricate ciliates to long-term warming: agglutinated forms decrease while hyaline forms increase - Yunfan Zhang; Wenhua Bian; Hanyue Chen; Wuchang Zhang; Chaofeng Wang; Jichen Qiu; Xiaoxia Sun; Jun Lin; Ying Yu; Meiping Feng; Bingzhang Chen (Marine Biology, 2026)

Fast solar-heating sponge with TEMPO-modified PDA coating for rapid recovery of highly-viscous oil on water - Jichen Huang; Xiaoyun Sun; Jinfeng Mei; Xudong Zheng; Zhongyu Li (Journal of Environmental Chemical Engineering, 2026)

Boosting exciton dissociation and charge transfer by precisely regulating the bridging location of rigid pyridine linkages in COFs for high-efficiency H2O2 photosynthesis - Hui Zhao; Jichen Su; Bao Lu; Jiawei Zhang; Minlei Zhang; Xinyu Sun; Lizi Liu; Xin Xu; Yao Wang; Hongyan Miao; Haiyan Zhu; Yuming Dong; et al. (Chemical Engineering Journal, 2025)

Mathematical modeling and connectivity-enhanced segmentation of void fraction in two-phase flow CT images - Zirou Jiang; Shuo Xu; Jiahao Chang; Jichen Miao; Yuewen Sun (Annals of Nuclear Energy, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Distribution characteristics and ecological risk assessment of heavy metal pollution in seawater near the Yellow River Estuary of Laizhou Bay - Xiaojie Jin; Jichen Liu; Liming Wang; Xiaoxiao Yu; Jiaying Wang; Yang Jin; Shaonan Qiu; Jiaqi Liu; Yuting Zhao; Shan Sun (Marine Environmental Research, 2025)

Effect of magnetic field on thorium ions electrochemical behavior in LiCl-KCl-CsCl low-temperature molten salt - Jichen Xu; Yujia Sun; Peipei Xing; Zhixuan Yi; Daoqing Ma; Xiaoli Tan; Ming Fang (Chemical Engineering Journal, 2025)

Asymmetric linear conjugated polymers for stable H2O2 photosynthesis via internal polarization - Yunfan Yang; Yuming Dong; Wenwen Chi; Xinyu Sun; Jichen Su; Xinying Chen; Hui Zhao; Yongfa Zhu (Chemical Engineering Journal, 2025)

Interactions between soil bacterial communities, assembly processes and microbial functions along the elevational gradient - Donghui Zhao; Congcong Shen; Zhi-Ming Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (CATENA, 2024)

Simultaneous aerobic nitrogen and phosphate removal capability of novel salt-tolerant strain, Pseudomonas mendocina A4: Characterization, mechanism and application potential - Hu Shu; Yonghao Ma; Huijie Lu; Huiming Sun; Jichen Zhao; Zhuohao Ruan; Jiayi Zhou; Yuting Liu; Fengkun Liu; Jingxuan Xu; Yazhi Zheng; Hui Guo; et al. (Bioresource Technology, 2024)

Liquid-like slippery surface with passive-multi active strategy integration for anti-icing/de-icing - Zhao Zehui; Wang Zelinlan; Liu Guang; Chen Dengke; Zhang Kaiteng; Zhu Yantong; Chen Jichen; Sun Shize; Liu Xiaolin; Chen Huawei (Chemical Engineering Journal, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

A genetic linkage map of the Pacific white shrimp (Litopenaeus vannamei): QTL mapping for low-temperature tolerance and growth-related traits and identification of the candidate genes - Huijie Lu; Wei Chen; Fengkun Liu; Minwei Huang; Kai Peng; Jichen Zhao; Xiaoying Chen; Yuping Sun; Chaozheng Li; Yihong Chen; Zhenxing Liu; Huo Li; et al. (Aquaculture, 2023)

The effect of “Fishery-PV Integration” on Penaeus monodon culture and research on the micro-ecological environment - Minze Liao; Xinxin Long; Zihao He; Jichen Zhao; Xieyan Chen; Dongwenjun Zhu; Chengbo Sun (Frontiers in Marine Science, 2022)
“Fishery-photovoltaic (PV) Integration” is a novel aquaculture model that provides enormous potential for aquaculture development. However, research on the aquaculture environment and organisms under the “Fishery-PV Integration” mode is presently sparse. This study investigated Penaeus monodon as a model, studying the growth rates of shrimp, water quality conditions, and the micro-ecological environment. After 105 days of rearing, P. monodon (initial weight of 0.006 ± 0.001 g) reached an average body weight of 11.69 ± 0.92 g. The water quality was stable (C( NH 4 + ) ≤ 1.57 mg/L) during the experimental period. The 16S rRNA gene sequencing results showed that bacterial community structures were significantly distinct among water, effluent and intestinal environments, with a closer relationship between the microbiotas in effluent and water. The dominant phyla present in shrimp intestines, water, and effluent were Proteobacteria, Actinobacteriota, and Bacteroidota. Likewise, Ralstonia , Candidatus Aquiluna , and Vibrio were the dominant genus in the three groups. The relative abundance of Vibrio as a common opportunistic pathogen for shrimp was relatively low, which is beneficial to promote the healthy growth of shrimp. The function of the “Fishery-PV Integration” microbiota was investigated using metagenomic technology. Results showed that microorganisms played an essential role in regulating intestinal amino acids, carbohydrate, and energy metabolisms. Antibiotic resistance genes (ARGs) data indicate that tetH , QnrVC6 and tetX were dominated ARGs in the intestine. At the same time, the ARGs with the highest relative abundance in the water and effluent groups were MexL and adeF . Notably, only 123 ARGs were identified within the “Fishery-PV Integration” pond. This outcome is significantly lower than other studies, indicating that shrimp cultured in the “Fishery-PV Integration” pond had a higher level of food safety. The current study describes the characteristics of the microflora and ARGs distribution in the “Fishery-PV Integration” pond for the first time, providing fundamental information for formulating management strategies for the whole microflora to maintain the health of shrimp.

Metagenomic Analysis of Bacterial Communities and Antibiotic Resistance Genes in Penaeus monodon Biofloc-Based Aquaculture Environments - Xieyan Chen; Zihao He; Jichen Zhao; Minze Liao; Yuan Xue; Jianing Zhou; Rowena Hoare; Sean J. Monaghan; Na Wang; Huanying Pang; Chengbo Sun (Frontiers in Marine Science, 2022)
Biofloc technology (BFT) is one of the most promising technologies in global aquaculture for the purpose of improving water quality, waste treatment, and disease prevention in intensive aquaculture systems. However, characterization of the microbial species and antibiotic resistance potentially present in biofloc-based aquaculture environments is needed. In this study, we used high-throughput sequencing technology to comprehensively compare the bacterial communities in mariculture ponds of Penaeus monodon ( P. monodon ), by testing of water, biofloc, and intestine of P. monodon . Operational taxonomic units (OTUs) cluster analysis showed that the nine samples tested divided into 45 phyla and 457 genera. Proteobacteria was the dominant bacteria in water, biofloc and prawn intestine. In biofloc and intestine, the Ruegeria (2.23–6.31%) genus represented the largest proportion of bacteria, with Marivita (14.01–20.94%) the largest group in water. Microbial functional annotation revealed that in all the samples, genes encoding metabolism were predominant. The antibiotic resistance gene annotation showed the highest absolute abundance of patB , adeF , OXA-243 , and Brucella_suis_mprF from Proteobacteria . PatB (11.33–15.01%), adeF (15.79–18.16%), OXA-243 (35.65%), and Brucella_suis_mprF (10.03%) showed the highest absolute abundance of antibiotic resistance genes in water, biofloc, and intestines, respectively. These findings may greatly increase our understanding of the characteristics of the microbiota of shrimp biofloc-based aquaculture systems and the complex interactions among shrimp, ambient microflora, and environmental variables. It provides a reference basis for policy on breeding, environmental safety, and maintaining food safety in the production of P. monodon .

Isobaric Tags for Relative and Absolute Quantitation-Based Proteomics Analysis Provides a New Perspective Into Unsynchronized Growth in Kuruma Shrimp (Marsupenaeus japonicus) - Jichen Zhao; Minze Liao; Zexu Lin; Yiyi Huang; Yunqi Zhong; Luyao Liu; Guoliang Chen; Zuotao Ni; Chengbo Sun (Frontiers in Marine Science, 2021)
Unsynchronized growth is a common phenomenon in farmed crustaceans. The underlying molecular mechanism of unsynchronized growth of crustaceans is unclear. In this study, a comparative proteomic analysis focusing on growth differences was performed using kuruma shrimp Marsupenaeus japonicus , an economic crustacean species, as the model. The study analyzed kuruma shrimp at fast growth stage and steady growth stage from both fast growth group and slow growth group by an Isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative proteomic analysis method. A total of 1,720 proteins, including 12,291 peptides, were identified. Fifty-two and 70 differentially expressed proteins (DEPs) were identified in the fast growth stage and steady growth stage, respectively. Interestingly, 10 DEPs, including 14-3-3-epsilon-like, GPI, GPD1, MHC-1a, and MHC-1b, were presented in both growth stages. In addition, all these 10 DEPs shared the same expression tendency at these two growth stages. The results indicated that these 10 DEPs are potential growth biomarkers of M. japonicus . Proteins associated with faster growth of M. japonicus may promote cell growth and inhibit cell apoptosis through the Hippo signaling pathway. The fast growth group of M. japonicus may also achieve growth superiority by activating multiple related metabolic pathways, including glycolysis, glycerophospholipid metabolism and Citrate cycle. The present study provides a new perspective to explore the molecular mechanism of unsynchronized growth in crustacean species.

Transcriptome Analysis Provides New Insights into Host Response to Hepatopancreatic Necrosis Disease in the Black Tiger Shrimp Penaeus monodon - Jichen Zhao; Xieyan Chen; Zihao He; Guoliang Chen; Zhaojian Lin; Yongkui Liu; Chengbo Sun; Wei Wang (Journal of Ocean University of China, 2021)

An efficient method for multigene co-interference by recombinant Bombyx mori nucleopolyhedrovirus - Hao Zheng; Feifei Ren; Qiuyuan Lu; Zhenming Cao; Jichen Song; Min Feng; Jisheng Liu; Jingchen Sun (Molecular Genetics and Genomics, 2019)

Characterization of bacterial communities associating with larval development of Yesso Scallop (Patinopecten yessoensisis Jay, 1857) by high-throughput sequencing - Xueying Sun; Jichen Liu; Ming Li; Xuewei Zhao; Jun Liang; Pihai Sun; Yuexin Ma (Journal of Ocean University of China, 2016)